Analisis Digital Marketing Tiktok Live sebagai Strategi Memasarkan produk UMKM Anjab Store - Gunawan Aji; Fatimah, Siti; Fatkhul Minan; Muhammad Aufal Azmi (Jurnal Bisnis dan Pemasaran Digital, 2022)
Purpose: This study aims to analyze digital marketing strategies through the TikTok Live platform and its contribution to increasing sales of UMKM Anjab Store products. Method: The research method used is descriptive qualitative with a case study approach. Data was collected through interviews with Anjab Store business owners, as well as analysis of TikTok Live content and product sales reports. Result: The results of the study show that Anjab Store has successfully implemented the TikTok Live marketing strategy by using TikTok influencers, special promos, special effects and filters, as well as interactive and entertaining live streaming sessions. TikTok Live's marketing contribution to increasing sales of Anjab Store products reaches 10 million rupiah per month. Limitation: This study also identifies limitations and suggestions for further studies regarding the development of digital marketing strategies on the TikTok Live platform for MSME products. Contribution: This research is expected to provide insights and recommendations for MSMEs in utilizing the TikTok social media platform as an effective marketing tool.